Starbucks Company Marketing Strategy in Facing the Covid-19 Pandemic: Case Study Report 2020 - Hakim, Abi Azizul; Mulyani, Ana Susi (PT FORMOSA CENDEKIA GLOBAL, 2024)
Starbucks is a global coffeehouse company known for its high-quality products and exceptional customer experience. However, the Covid-19 pandemic has had a significant negative impact on Starbucks' business, such as decreased sales, store closures and changes in consumer behavior. To overcome these challenges, Starbucks has implemented several effective marketing strategies, such as adapting product offerings, strengthening digital engagement, increasing customer loyalty, and expanding market reach. This case study aims to analyze the marketing strategy of the Starbucks company in facing the Covid-19 pandemic, based on their 2020 annual report. This case study uses a qualitative descriptive method, by collecting secondary data from the Starbucks annual report and other relevant sources. The results of this case study show that Starbucks' marketing strategy has succeeded in helping them maintain business performance, meet customer needs and expectations, and prepare for a better future.